Application of Equivalent Circuit Models to Monitor the Degradation of Organic Photovoltaic Cells - Sesa, Elisa; Ulum, Muhammad Syahrul; Darwis, Darmawati; Sulaiman, Kasman (Makara Journal of Science, 2015)
Organic photovoltaic (OPV) devices have lower efficiency, shorter lifetimes, faster degradation, and poorer stability than inorganic photovoltaics (IPV) in ambient conditions. In this paper, the equivalent electrical circuit of a two-diode model effectively extracts the model-fit electrical photovoltaic (PV) parameters from degraded OPV devices, especially the series (Rs) and shunt (Rsh) resistances. The result shows a better correlation between the resistances of the devices and performance of the devices over the degradation process where the devices are deliberately exposed to ambient conditions under constant illumination. The degradation of the devices is mostly caused by the degradation of the aluminum (Al) electrode from water and oxygen, which correlates to the Rs. However, it is possible that the degradation of the bulk active layer can also occur due to the constant illumination on the device, which causes a reduction of photocurrent.